2015
DOI: 10.18671/scifor.v43n108.20
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades físicas do solo e crescimento de eucalipto implantado em diferentes métodos de preparo do solo

Abstract: ResumoO objetivo do estudo foi verificar alterações nas propriedades físicas de um Argissolo Vermelho-Amarelo distrófico arênico e no crescimento de Eucalyptus grandis, implantado em diferentes métodos de preparo do solo, após 6 anos. O experimento foi realizado na Fundação Estadual de Pesquisa Agropecuária, em Santa Maria, Rio Grande do Sul. O delineamento experimental utilizado foi blocos ao acaso com três repetições e quatro tratamentos: coveamento manual, escarificado, escarificado mais grade niveladora e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
3
2
0
6
Order By: Relevance
“…The decreasing linear behavior shown in Figure 2 describes the way the described phenomenon is also reflected in the total porosity of the soil, indicating a reduction in the values of this variable when PR increases. This result agrees with Rocha et al (2015), who also found that increasing soil density and penetration resistance reduced TP. Figure 3 shows the relationships between PR, macroporosity (Ma) and microporosity (Mi).…”
Section: Resultssupporting
confidence: 92%
“…The decreasing linear behavior shown in Figure 2 describes the way the described phenomenon is also reflected in the total porosity of the soil, indicating a reduction in the values of this variable when PR increases. This result agrees with Rocha et al (2015), who also found that increasing soil density and penetration resistance reduced TP. Figure 3 shows the relationships between PR, macroporosity (Ma) and microporosity (Mi).…”
Section: Resultssupporting
confidence: 92%
“…Macroporosity values in all studied management systems and layers were above the critical limit of 0.10 m³ m -3 , similar to the findings reported by and Rocha et al, (2015), who demonstrated that macroporosity values above this limit indicate favorable plant growth and root development conditions.…”
Section: Discussionsupporting
confidence: 89%
“…Nesse caso, os sistemas de manejo devem ter por objetivo condições adequadas a um satisfatório crescimento das florestas plantadas, aliado à conservação do solo. Rocha et al (2014) observaram um menor crescimento de plantas de eucalipto um uma área de solo argiloso quando foi adotado manejo sem revolvimento inicial do solo, o que foi relacionado à densidade do solo. Por sua vez o comportamento da densidade do solo tem relação com a granulometria do solo e o relevo (CEDDIA et al, 2009) A geoestatística é utilizada em áreas de exploração silviculturais para avaliar a dependência espacial de atributos do solo, constituindo eficiente suporte ao manejo do solo, da água e da vegetação, propiciando intervenções baseadas em mapas de isovalores das variáveis de interesse (CAVALCANTE et al, 2011…”
Section: Introductionunclassified